ULTRASOUND GUIDED TUNNELLED CUFFED CATHETER PLACEMENT WITHOUT FLUOROSCOPIC GUIDANCE BY ANATOMICAL LANDMARKS; ACCURACY AND SAFETY - Wahaj, Wahaj; Azam, Malik Nadeem; Butt, Batool; Salahuddin, Salahuddin; Tahir, Taleah; Khan, Nudrat Jehangir; Rahman, Muhammad Khalid; Raja, Khalid Mehmood; Arshad, Abdul Rehman; Mir, Abdul Wahab (Journal of Ayub Medical College Abbottabad, 2019)
Background: Chronic kidney disease is a growing disease with high morbidity and mortality. Haemodialysis remains the most common option available for all those not planning for renal transplantation. Vascular access is the most important aspect of haemodialysis. Though not recommended but central venous catheters remain the most common vascular access in starters on haemodialysis. There is a growing trend towards placement of tunnelled cuffed catheters (TCC). TCC placement requires fluoroscopic guidance which is not available in all centres. The rationale of this study was to describe safety and accuracy of a catheter placement technique not dependent on fluoroscopic guidance for resource limited settings. Methods: Dialysis dependent patients of a single hospital without long term vascular access were selected over a period of 15 months after getting informed written consent. A new technique was described in which depth of catheter was estimated by superficial anatomical and ultrasound guided measurements for TCC placement which were checked by conventional chest radiography post procedure. Results: A total of 209 catheters were placed over a period of 15 months, 189 males and 30 females. Various sites were used predominantly right Internal jugular vein (IJV) (85.6%). Overall success rate was 97.1% (98.3% males, 90% females, p=0.08). Right IJV was successful 98.9%, left IJV 87.5% (p<0.001). Multiple thrombosed/stenosed veins were associated with higher failure rate (p<0.001). Conclusion: TCC can be placed successfully and safely in right IJV under ultrasound guidance using anatomical landmark measurement technique without fluoroscopic guidance. Keywords: Chronic Kidney Disease; Haemodialysis; Central Venous Catheter; Tunnelled Cuffed Catheter; Anatomical Landmarks; Carina; Fluoroscopy; Chest Radiograph